The diagnosis and management of alopecia - M.H. Motswaledi; K. Mathekga (South African Family Practice)
Alopecia refers to loss of hair from the scalp or other hair-bearing areas of the body. Alopecia has a significant impact on quality of life. It is commonly associated with loss of self-esteem and emotional stress. It can be non-scarring (noncicatricial) and reversible, or scarring (cicatricial) and often permanent.